The Effect of Physico-Chemical Properties of Aquatic sediment to the Distribution of Geochemical Fractions of Heavy Metals in the Sediment - Barlah Rumhayati; Catur Retnaningdyah; Novi Anitra; Ahmad Dodi Setiadi (UNEJ e-Proceeding, 2016)
Heavy metals in the aquatic sediment could be fractioned into five geochemical fractions. Assessment of these fractions is valuable to determine the bioavailable metals provided by the aquatic sediment. Physico-chemical properties of sediment determine the distribution of the fractions. The aims of this research were to determine the physico-chemical properties of sediment sample and to determine its effect to the distribution of heavy metals fraction. Sediment samples were collected from the Porong River at two stations by using Eickman Grab sampler. The samples were stored in 4oC until analysis. Physico-chemical properties of sediment were investigated, including texture, pH, salinity, cationic exchange capacity (CEC), redox potential, and organic material concentration. The geochemical fractions of heavy metals (Pb, Cu, and Zn) were determined after sequential extraction using modified BCR method. As a result, texture of sediment correlated to the organic material concentration while the amount of organic material determines the third fraction of heavy metals, i.e. the oxidation fraction. CEC and pH, and salinity determined the amount of the first fraction, i.e. the exchangeable fraction. Redox potential of sediment affected the amount of the second fraction of heavy metals, i.e. the   acid reducible fraction.